(untitled) (Issues in Social and Environmental Accounting (ISEA), 2025)
This concept paper examines how digitalization strengthens the detection and prevention of tax evasion in Malaysia by focusing on three key dimensions: tax automation, artificial intelligence (AI) and big data analytics, and the expansion of the digital economy. Grounded in Economic Deterrence Theory, the paper explores how digital tools enhance tax compliance by increasing the probability of detection and altering taxpayer behaviour. Through a qualitative review of current literature, institutional developments, and policy initiatives, the study highlights the positive contributions of systems such as MyTax, e-Invoicing, and AI-driven data analytics in improving transparency, reducing information asymmetry, and enhancing enforcement capacity. The paper also identifies emerging challenges, including cross-border digital transactions, profit-shifting risks, and gaps within existing regulatory frameworks. It concludes by proposing policy recommendations to improve digital infrastructure, strengthen international cooperation, and align Malaysia’s tax administration with global standards to support a more resilient, equitable, and future-ready tax system.